Bevacizumab in the treatment of breast cancer. Issue 10 (October 2008) - Sirohi, Bhawna; Smith, Katy
The monoclonal antibody bevacizumab, targeted against the angiogenesis factor VEGF has clinical activity against several common cancers. In metastatic breast cancer it improves response rate and time to progression in combination with paclitaxel/docetaxel compared with paclitaxel/docetaxel alone; the drug is currently being investigated in other combination regimens and as adjuvant and neoadjuvant therapy in early breast cancer. It is generally well tolerated. Side effects, including hypertension, proteinuria, thrombosis and bleeding, are uncommon and usually managed easily. Based on the clinical efficacy of bevacizumab, other small-molecule oral antiangiogenesis agents are now also under development.